A Comparative Study on Efficacy of Amoxicillin and Azithromycin in Prevention of Postoperative Sequelae Following Third Molar Surgery - Gurung, Rashmi Shakya; Bimb, K.; Shrestha, D. (Nepal Medical College Journal, 2019)
Amoxicillin is the commonly prescribed antimicrobial for prevention of post-operative complications following surgical extraction of mandibular third molar. However recently, the use of macrolideantibiotics had been encouraged in dentistry. The aim of this study was to compare the efficacy of Amoxicillin and Azithromycin in preventing post-operative sequelae following third molar surgery. An open- labeled randomized controlled study was carried out in Department of Oraland Maxillofacial surgery, college of Dental Sciences and Hospital, Nepal Medical College (CODSHNMC), Attarkhel, Kathmandu, Nepal from May 2018 to June 2019. One hundred and twenty patients undergoing surgical extraction of impacted mandibular third molar were randomized by lottery method into two groups: Group A received Amoxicillin and Group B received Azithromycin. Both the groups were assessed postoperatively on 1st, 3rd and 7th days for post-operative complications- pain, swelling, trismus and pus discharge. The present study revealed no significant differences between the efficacy of Amoxicillin and Azithromycin in preventing postoperative sequelae following surgical extraction of impacted third molar. Amoxicillin and Azithromycin were therefore found to be equally effective. Thus, Azithromycin can be used as an alternative drug to Amoxicillin in case of resistance and intolerance to Amoxicillin.